All police: a platform to issue Fines - Mebrak, Mahdi; Zakkar, Chaima; Benazi, Makhlouf: Supervisor (University Mohamed Boudiaf of M’sila, Faculty of Mathematics and Informatics, Department of Computer Science, 2024)
This dissertation presents the Traffic Bounty Hunter platform, an innovative solution addressing traffic violations and enhancing road safety in Algeria. The platform combines a mobile app for citizen reporting with a web interface for law enforcement validation. Our research explores theoretical foundations of traffic safety, citizen engagement, and existing technologies, forming the basis for the platform's architecture. UML diagrams detail the system's structure and component interactions. The technology stack (React Native, React.js, Firebase Firestore) ensures scalability and performance. Features include a gamified reward system, encouraging citizens to become "traffic bounty hunters," and a decentralized evaluation process involving multiple officers for fair assessment. Despite challenges in server development and monetary transactions, the project achieved significant milestones in user interface design and database implementation. This research contributes to traffic safety management by demonstrating a viable citizen-centric approach to violation reporting and fine issuance.
Keywords: Traffic Bounty Hunter; citizen reporting; law enforcement; traffic violations; road; safety; mobile application; web interface; gamification; decentralized evaluation; fine issuance; all police